2018
DOI: 10.3892/or.2018.6608
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous carbon dioxide application suppresses bone destruction caused by breast cancer metastasis

Abstract: Hypoxia plays a significant role in cancer progression, including metastatic bone tumors. We previously reported that transcutaneous carbon dioxide (CO2) application could decrease tumor progression through the improvement of intratumor hypoxia. Therefore, we hypothesized that decreased hypoxia using transcutaneous CO2 could suppress progressive bone destruction in cancer metastasis. In the present study, we examined the effects of transcutaneous CO2 application on metastatic bone destruction using an animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…In their work, the mice had hypoxia stress (8% O 2 ) for 10 h followed by 3 h of reoxygenation. The induction of hypoxia condition to tissues in a study by Takemori et al (2019) was unique compared to the others since it did not involve manipulating O 2 content in the air but through applying CO 2 hydrogel to corresponding tissue [ 24 ]. The number of animals used per group in these four studies ranged from six to 10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, the mice had hypoxia stress (8% O 2 ) for 10 h followed by 3 h of reoxygenation. The induction of hypoxia condition to tissues in a study by Takemori et al (2019) was unique compared to the others since it did not involve manipulating O 2 content in the air but through applying CO 2 hydrogel to corresponding tissue [ 24 ]. The number of animals used per group in these four studies ranged from six to 10.…”
Section: Resultsmentioning
confidence: 99%
“…N/BS), and the number of osteoclasts/total area (N. Oc/TA) [ 22 , 23 ]. On the other hand, osteoclast formation following hypoxia was also assessed based on the number of osteoclasts in the femur following TRAP [ 20 , 24 ]. In determining the impact of hypoxia on bone resorption systemically, the levels of bone resorption marker, C-telopeptide of type-1 collagen (CTX-I), in serum was measured [ 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34][35] Although this model has been instrumental in revealing molecular mechanisms underlying metastatic processes and translational studies for drug development, several problems remain because of its requirement for high technical proficiency to exactly insert a syringe needle into the left ventricle of a mouse, which causes severe cardiac stress and rapid mortality. 36,37 In the current study, we employed an intratibial injection model 38,39 because it is technically simple and suitable to investigate the longterm effects of drugs. Second, we found that GM-CDDP exerted strong antitumor effects in the bone metastatic mouse model using MDA-MB-231 human breast cancer cells, but we used only one breast cancer cell line in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Another example relates to the effects of this therapy on tumors. CO 2 therapy has been demonstrated to have inherent antitumor effects [3033] by suppressing metastasis [33, 34], enhancing the antitumor effect of radiation therapy [35, 36], and suppressing bone destruction caused by bone metastasis [37]. All of these are targets that warrant further examination in clinical trials.…”
Section: Discussionmentioning
confidence: 99%